Effect of hydroxyethyl starch 200/0.5 on von willebrand factor serum level and activated partial thromboplastin time (aptt) - Atmaja, Sarah Puspita; Khotib, Junaidi; Rahardjo, Eddy; Shinta, Dewi Wara; Rahmadi, Mahardian; Suprapti, Budi (Folia Medica Indonesiana, 2016)
Hydroxyethyl starch (HES) is a colloid administered frequently for intravascular volume expansion during perioperative period. Impairment of haemostasis have been reported during HES administration, but the volume of solution administered was usually higher than 20 ml.kg-1. The objective of this study was to evaluate the effect of Hydroxyethyl starch 200/0.5 dose less than 20 ml.kg-1 on von Willebrand factor serum level and activated partial thromboplastin time. A prospective, observational study was conducted to evaluate von Willebrand factor and activated partial thromboplastin time of patients receiving Hydroxyethyl starch 200/0.5. Inclusion criteria were patients undergoing elective surgery who were going to receive Hydroxyethyl starch 200/0.5 intraoperatively. Fourty six patients were divided into patients receiving crystalloid only group (n=23 patients) and hydroxyethyl starch (n=23 patients). Coagulation variables were assesed 30 minute after insicion and 60 minute after infusion of crystalloid or colloid. Measurement of von Willebrand within each group after crystalloid or HES 200 infusion showed significant decrease, from (mean±SE) 97.688±15.219 ng/ml to 31.611±10.058 ng/ml (p< 0.001) in crystalloid group and 92.884±15.208 ng/ml to 27.378±6.399 ng/ml (p<0.001) in HES 200 group. Activated partial thromboplastin time change was statistically significant (mean±SE) 31.27±1.39 to 35.61±1.62 in HES group only (p=0.007), but this change was not clinically significant. In conclusion, there was neither significant difference in von Willebrand serum level nor in activated partial thromboplastin time between the two groups. There was no coagulation influence with clinically significant effect in the use of HES 20 ml/kg BW in patients undergoing elective surgery.